The effects of a land-based warm-up and accompanying passive heat retention on core body temperature, hormones, and subsequent performance in elite surfers - Cook, C. J.; Serpell, B. G.; Hanna, L. J. (Frontiers in Sports and Active Living, 2024)
Surfing is a high participation sport, yet little sport science research exists regarding competitive performance in surfing. Given surfing's inclusion as an Olympic sport from the 2020 Tokyo Olympics onwards, an examination of performance would seem useful. In numerous land-based sports, and in swimming, the importance of a warm-up and muscle heat is well documented. However, surfing is a unique sport in that it is undertaken both above and below water. Therefore, the aim of this study was to explore the effectiveness of a warm-up in terms of readiness to perform in surfing. We discuss this in the context of thermal regulation, hormone profile change, and the subsequent expression of "power" on waves—a key criteria that surfers are scored for. Nineteen advanced level surfers (i.e., competitive at just below national level in Australia; n = 15 males and n = 4 females) with mean (±SD) age, height, and weight of 24.5 ± 11.6 years, 174.7 ± 9.1 cm, and 67.7 ± 10.2 kg, respectively, were recruited. We adopted a repeated measures pre- and post-design whereby participants engaged in several simulated surfing competitions in an artificial wave pool; once after an active warm-up combined with a passive heat retention strategy (i.e., wrapping themselves in survival blankets—treatment), and once after no warm-up (control). Saliva samples were collected pre- and post-active warm-up, or at equivalent times under control conditions, for the measurement of testosterone and cortisol. Increases in these hormones have previously been associated with an enhanced readiness to compete. Our results demonstrate a clear thermoregulatory benefit from the treatment, with the participants` core body temperatures typically higher from the end of the warm-up to the end of the surf session following treatment (p = 0.03), and a magnitude of increase in core body temperature once in the water that is greater following treatment (p = 0.01). A small magnitude upward change in testosterone (p = 0.01) and cortisol (p = 0.001) following warm-up was also observed. Finally, warm-up was associated with an improved wave performance compared with the control, with a 20% increase in the performance score typically observed (p = 0.01). We argue that the improved thermal profile may have influenced power and, as such, surfing performance was enhanced.